The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.5039/agraria.v8i4a3150
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento, produtividade e nível crítico de fósforo para o quiabeiro em relação à adubação fosfatada

Abstract: RESUMO Growth, yield and phosphorus critical level for okra in relation to phosphate fertilization ABSTRACTThe study aimed to evaluate the growth, productivity attributes and soil P critical level, for okra cultivar, Clemson Spineless, regarding phosphorus fertilization at the seeding. The research was conducted under field conditions, in the Zona da Mata of Pernambuco state, Brazil. The experimental design was a randomized block with six replications. Treatments consisted of doses 0, 8, 16, 32, 65, 130 and 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
2
2
0
Order By: Relevance
“…The results are consistent with those obtained by Oliveira et al (2013), who studied the okra cv. Clemson Spineless 80; they observed an increase in fruit diameter with increased phosphorus fertilization.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The results are consistent with those obtained by Oliveira et al (2013), who studied the okra cv. Clemson Spineless 80; they observed an increase in fruit diameter with increased phosphorus fertilization.…”
Section: Resultssupporting
confidence: 93%
“…The results showed that the dose of 80 kg/ha of phosphorus provided the maximum productivity values, while the treatment without phosphorus fertilization showed minimum productivity values. Oliveira et al (2013), working with the Clemson Spineless 80 cv., also found positive effects of P on increasing okra yield.…”
Section: Resultsmentioning
confidence: 99%
“…The maximum length (17.3 cm) and number of fruits (26.6 fruits plant -1 ) were estimated at the dose of 80 kg ha -1 P 2 O 5 . The increase in the number of fruits per plant as a function of the increase in the P dose has also been observed by Oliveira et al (2007), Firoz (2009), Oliveira et al (2013) and Uddin et al (2014). Regarding the absence of phosphate mineral fertilizer at planting, there were increases of 4.8 and 37.1% in length and number of fruits, respectively, at the optimal dose of P.…”
Section: Resultssupporting
confidence: 67%
“…For example, Matos et al (2020) evaluated okra yield as a function of cattle manure doses. For the conditions of the Northeast, there are studies evaluating phosphate fertilization (OLIVEIRA et al, 2013;SANTOS et al, 2019), nitrogen and potassium fertilization (SANTOS et al, 2019), and organomineral fertilization (OLIVEIRA et al, 2014;SANTOS et al, 2019;SALES et al, 2020;SALES et al, 2021).…”
Section: Introductionmentioning
confidence: 99%